Land grabbing or value grabbing? Land rent and wind energy in the Isthmus of Tehuantepec, Oaxaca. (July 2022) - Alonso Serna, Lourdes
The Isthmus of Tehuantepec in Oaxaca is the first region in Mexico with a large-scale wind energy development. The region holds 60% of the country's installed capacity, but the new infrastructure has faced opposition from sectors of the local population concerned about wind farms' social and environmental impacts. The opposition and ensuing conflicts have been widely studied; some of these studies have framed wind energy as part of the recent cycle of land grabbing. Nevertheless, this literature has overlooked landholders' acceptance of wind energy. This paper aims to address this gap and argues that the main driver of the land grabbing process is land rent. The paper draws on recent insights from political ecology that highlight that the commodification of nature is predicated on rent. The paper uses the notion of value grabbing to look at the social struggles over property rights in the Isthmus and the conflicts for the increase and distribution of rents from wind energy.